Teachers' Perceptions of Inadequate Outdoor Play Among Preschool Children in Aba, Abia State, Nigeria - Emmanuel Lucas Nwachukwu; Nwamaka Goodness Egbue; Ijeoma VictorNwakaku; Unegbu Lasbrey Ikechukwu (JF Publisher, 2026)
Growing global and national concerns highlight the declining opportunities for outdoor play in early childhood education, despite its established importance for children’s holistic development. In many Nigerian preschool settings, increasing academic demands, safety concerns, and infrastructural limitations have reduced the emphasis on play-based learning. This study examined preschool teachers’ perceptions of inadequate outdoor play provision in Aba, Abia State, Nigeria, with focus on availability, developmental implications, and implementation constraints. A descriptive survey design was adopted. The population comprised 453 teachers in registered public and private preschools. Using multistage sampling informed by Yamane’s formula (5% margin of error), 212 questionnaires were distributed, of which 200 valid responses were analyzed. Data were analyzed using descriptive statistics and chi-square tests. Findings revealed that outdoor play provision is generally inadequate, characterized by limited space, restricted daily access, insufficient time allocation, and safety concerns (cluster mean = 2.26). Teachers agreed that constrained outdoor play negatively affects children’s physical activity, peer interaction, classroom behaviour, and attention regulation (cluster mean = 3.47). No significant subgroup differences were observed. The study identifies a disconnect between teachers’ recognition of the developmental value of outdoor play and the structural conditions influencing its implementation. It underscores the need to strengthen facility standards and reinforce play-based pedagogy in early childhood education settings.